2001
DOI: 10.1067/mtc.2001.112824
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral skeletonized internal thoracic artery grafts in patients with diabetes mellitus

Abstract: Bilateral skeletonized internal thoracic artery grafting is a good surgical revascularization option in diabetic patients. Operative mortality and prevalence of sternal infection are comparable with those of nondiabetic patients. However, the risk of sternal infection in obese diabetic women is high, and for them we advocate the use of a single artery instead of bilateral internal thoracic arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 30 publications
(27 reference statements)
8
90
1
5
Order By: Relevance
“…The use of arterial grafts in coronary revascularization was not recommended for diabetic patients in previous reports, 3,4,30 because this method was thought to increase complications such as mediastinitis. We recommend skeletonizing the IMA graft, because we found that this method of dissecting IMA graft may lower the risk of complications.…”
Section: Endo Et Al Bilateral Imas For Diabetes 1347mentioning
confidence: 99%
“…The use of arterial grafts in coronary revascularization was not recommended for diabetic patients in previous reports, 3,4,30 because this method was thought to increase complications such as mediastinitis. We recommend skeletonizing the IMA graft, because we found that this method of dissecting IMA graft may lower the risk of complications.…”
Section: Endo Et Al Bilateral Imas For Diabetes 1347mentioning
confidence: 99%
“…Matsa et al (26) and Lev-Ran et al (27) also showed an increased incidence of sternal wound dehiscence in patients who were obese, female and diabetic, and recommended avoidance of the use of bilateral internal thoracic artery in this specific population. Other work has shown obesity and diabetes to be risk factors for the development of sternal wound dehiscence (1,4,11,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…MENEZES, AM ET AL -Technical aspects in skeletonization of the internal thoracic artery using an ultrasonic scalpel the morbimortality between the utilization of only one ITA or of both [19][20][21][22][23]. In our series, no cases of infections (osteomyelitis or mediastinitis) were observed even though electrocautery and bone wax were used for sternal hemostasis, when necessary.…”
Section: -Final Aspect Of Skeletonized Internal Thoracic Arterymentioning
confidence: 97%